Eksplorasi Penggunaan Metode Pembelajaran Berbasis Proyek dalam Meningkatkan Hasil Belajar Ilmu Pengetahuan Alam Siswa Sekolah Dasar Negeri 101930 Perbaungan - Sri Delima; Thessa Herdyana; Layil Safitri (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2026)
Project-Based Learning has emerged as an effective instructional approach for promoting meaningful learning by actively engaging students in authentic, collaborative, and problem-oriented activities. This study investigates how the Project-Based Learning method was implemented in science instruction for fifth-grade students at Elementary School Negeri 101930 Perbaungan and examines its influence on learning outcomes and the perceptions of students and teachers regarding its application. The research employed a descriptive qualitative design involving 14 fifth-grade students as the unit of analysis. Data were collected through classroom observations during a project involving the construction of a simple periscope, semi-structured interviews with the classroom teacher and school principal, and documentation of learning activities and students' academic records. The findings demonstrate that Project-Based Learning substantially improved student learning outcomes, as reflected by an increase in classical learning mastery from 7.1% before implementation to 100% at the final stage, while the class average score improved from 56.5 to 85.7. The method also strengthened students' intrinsic motivation, collaborative learning, and critical thinking through authentic and hands-on learning experiences. The study concludes that Project-Based Learning is an effective pedagogical strategy for enhancing science learning achievement while fostering essential twenty-first-century competencies in elementary school students.